The Transformation of Civil Judgment Execution Toward Court Excellence in Indonesia - Ramadhan, Said; Pradana, Vega Gilang; Latifiani, Dian; Yustina Dhian Novita (Law and Justice, 2025)
This study discusses the transformation of civil judgment execution as a crucial step toward achieving Court Excellence in Indonesia. The main issue examined is the persistent challenges in enforcing civil court decisions, which often hinder the execution process. The objective of this study is to identify the core problems in civil execution, elaborate on the role of Court Excellence within Indonesia’s judicial system, and propose concrete measures to improve the efficiency and effectiveness of execution. The research employs a normative juridical method, using an analytical approach to legislation, legal doctrines, and relevant court decisions. The findings reveal that the primary obstacles in execution include unmet costs, third-party resistance, issues in the wording of judgments, the applicant’s inability to identify assets, undiscovered execution objects, and difficulties in executing court decisions. The transformation of civil execution involves improving the drafting of judgments, enhancing inter-agency coordination, implementing strict supervision, providing training and education, and establishing a special unit within the Supreme Court. The results of this study highlight the importance of transforming civil judgment execution as an integral part of the effort to achieve Court Excellence in Indonesia. This transformation is expected to enhance the efficiency and effectiveness of executions, build a more authoritative judiciary, and ensure justice and compliance with the law in society.   Penelitian ini membahas transformasi eksekusi putusan perdata sebagai langkah penting menuju Court Excellence di Indonesia. Isu utama yang diteliti adalah permasalahan pelaksanaan eksekusi putusan pengadilan perdata yang seringkali menghadapi tantangan yang menghambat prosesnya. Penelitian ini bertujuan untuk mengidentifikasi masalah utama dalam eksekusi perdata, menguraikan peran Court Excellence dalam sistem peradilan Indonesia, dan memberikan langkah-langkah konkret untuk meningkatkan efisiensi dan efektivitas eksekusi. Temuan penelitian ini mengungkapkan bahwa kendala utama dalam eksekusi meliputi biaya yang belum terpenuhi, perlawanan oleh pihak ketiga, permasalahan dalam redaksi putusan, ketidakmampuan pemohon eksekusi menunjukkan harta, objek yang ditunjukkan tidak ditemukan, dan kesulitan dalam melaksanakan eksekusi terhadap putusan pengadilan. Transformasi eksekusi putusan perdata melibatkan perbaikan dalam redaksi putusan, koordinasi yang lebih baik, pengawasan yang ketat, pelatihan dan edukasi, serta pembentukan unit khusus di Mahkamah Agung. Hasil penelitian ini menyoroti pentingnya transformasi eksekusi putusan perdata sebagai bagian integral dari upaya mencapai Court Excellence di Indonesia. Transformasi ini diharapkan akan meningkatkan efisiensi dan efektivitas pelaksanaan eksekusi, menciptakan peradilan yang lebih berwibawa, dan memastikan keadilan serta kepatuhan terhadap hukum dalam masyarakat.